Understanding and Managing Zoonotic Risk in the New Livestock Industries - Liverani, M; Waage, J; Barnett, T; Pfeiffer, D; Rushton, J; Rudge, J; Loevinsohn, M; Scoones, I; Smith, R; Cooper, B; White, L; Goh, S; et al. (National Institute of Environmental Health Sciences, 2013)
BACKGROUND: In many parts of the world, livestock production is undergoing a process of rapid intensification. The health implications of this development are uncertain. Intensification creates cheaper products, allowing more people to access animal-based foods. However, some practices associated with intensification may contribute to zoonotic disease emergence and spread: for example, the sustained use of antibiotics, concentration of animals in confined units, and long distances and frequent movement of livestock. OBJECTIVES: Here we present the diverse range of ecological, biological, and socioeconomic factors likely to enhance or reduce zoonotic risk, and identify ways in which a comprehensive risk analysis may be conducted by using an interdisciplinary approach. We also offer a conceptual framework to guide systematic research on this problem. DISCUSSION: We recommend that interdisciplinary work on zoonotic risk should take into account the complexity of risk environments, rather than limiting studies to simple linear causal relations between risk drivers and disease emergence and/or spread. In addition, interdisciplinary integration is needed at different levels of analysis, from the study of risk environments to the identification of policy options for risk management. CONCLUSION: Given rapid changes in livestock production systems and their potential health implications at the local and global level, the problem we analyze here is of great importance for environmental health and development. Although we offer a systematic interdisciplinary approach to understand and address these implications, we recognize that further research is needed to clarify methodological and practical questions arising from the integration of the natural and social sciences.